Harmonizing the Hijri Calendar: A Comparative Insight of Indonesia's Imkān al-Ru’yah Crescent Visibility Criteria with Malaysia and Saudi Arabia - Fikri, Mursyid; Anas, Muh Fauzi; Lubis, Arjuna Hiqma; Indriana (Universitas Islam Negeri Alauddin Makassar, 2025)
The determination of the beginning of Hijri months in Indonesia reflects significant diversity, particularly in the methods adopted by different Muslim organizations. This study aims to examine the potential conflicts arising from the implementation of the new Imkān al-Ru’yah criteria in Indonesia and to compare them with the criteria used in Saudi Arabia and Malaysia. This research employs a qualitative approach, utilizing in-depth interviews and literature analysis. The collected data is analyzed through content analysis to understand the underlying factors contributing to the differences in Hijri month determination. The findings indicate that the new Imkān al-Ru’yah criteria have intensified long-standing disputes due to variations in crescent visibility in the eastern hemisphere. Key discrepancies arise from differences in hisab criteria, interpretations of Islamic legal principles regarding Ulil Amri, and the symbolic meaning of the crescent moon. The study also reveals that Muhammadiyah’s KHGT criteria align with those of Saudi Arabia, whereas the new Mabims criteria differ from those of Saudi Arabia. This study provides a comparative analysis of Hijri month determination criteria across multiple countries, highlighting the underlying theological and astronomical factors that shape different methodologies. The research offers insights into the complexities of Hijri calendar determination in Indonesia and contributes to discussions on standardizing crescent sighting criteria. The findings may serve as a basis for fostering greater alignment among Islamic organizations and regional authorities.